Przygoda estetyczno-mentalna w przekładzie - Tokarz, Bożena (Przekłady Literatur Słowiańskich, 2018)
Aesthetic-Mental Adventure of Translation Translation is an adventure. The desire to experience it exceeds all other translation motives. It is a desire of a rational, pragmatic, emotional and physical nature. Therefore, full normalisation of the principles of artistic translation constantly encounters difficulties. Outside the borders of the scheme there is something called talent and empathy, understood as a cognitive-affective phenomenon. The paradigm of desire is defined by: individual weaknesses, ambition, desire to communicate, to know and experience something so far unknown, and the interaction between them in the form of surprise, dazzlement, and even shock. KEY WORDS: translation, adventure, empathy, intercultural communication, creativity of the interpreter — Tone Pretnar